2022
DOI: 10.1021/jacs.2c08884
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Catalyst Synthesis Strategies to Prepare Atomically Dispersed Fe-N-C Heterogeneous Catalysts

Abstract: We report a strategy to integrate atomically dispersed iron within a heterogeneous nitrogen-doped carbon (N-C) support, inspired by routes for metalation of molecular macrocyclic iron complexes. The N-C support, derived from pyrolysis of a ZIF-8 metal–organic framework, is metalated via solution-phase reaction with FeCl2 and tributyl amine, as a Brønsted base, at 150 °C. Fe active sites are characterized by 57Fe Mössbauer spectroscopy and aberration-corrected scanning transmission electron microscopy. The sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Importantly, the refined line width Γ = 0.30 mm s –1 in the Mössbauer spectra is similar to those routinely observed in molecular compounds. ,, This observation indicates that all of the iron sites have the same environment, especially since the quadrupole splitting of tetrahedral iron­(II) sites can be highly sensitive to small changes . This contrasts with reports of iron incorporated into other carbon nitride and other N-doped carbon materials, where fitting the Mössbauer data required the superposition of 3–4 subspectra, indicative of multiple iron environments and/or partial oxidation of the samples. , We attribute the uniformity of incorporated iron­(II) sites to the crystallinity of PTI, particularly the channels that can accommodate the iron ions without altering the lattice.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Importantly, the refined line width Γ = 0.30 mm s –1 in the Mössbauer spectra is similar to those routinely observed in molecular compounds. ,, This observation indicates that all of the iron sites have the same environment, especially since the quadrupole splitting of tetrahedral iron­(II) sites can be highly sensitive to small changes . This contrasts with reports of iron incorporated into other carbon nitride and other N-doped carbon materials, where fitting the Mössbauer data required the superposition of 3–4 subspectra, indicative of multiple iron environments and/or partial oxidation of the samples. , We attribute the uniformity of incorporated iron­(II) sites to the crystallinity of PTI, particularly the channels that can accommodate the iron ions without altering the lattice.…”
supporting
confidence: 59%
“…This has been demonstrated using Mössbauer spectroscopy, a technique that uses small shifts in the energy for γ-ray absorption by 57 Fe nuclei to report the local environment and oxidation state of the Fe ions . Though not all iron-impregnated carbon nitrides have been examined with Mössbauer spectro­scopy, ,,,,, in every case where Mössbauer spectra were recorded, these spectra indicate multiple iron environments. To our knowledge, the Mössbauer spectra of all N-doped carbon materials indicate a mixture of iron­(II) and iron­(III), and many also contain Fe oxides and Fe nanoparticles. Thus, it is not clear whether their reactivity stems from a single site, many sites, or undefined/impurity sites. Further, most carbon nitrides are amorphous, which gives additional ambiguity about the geometries of the Fe sites.…”
mentioning
confidence: 99%
“…The aerobic oxidation of a sulfonated hydroquinone (Figure C) was chosen as the catalytic probe reaction. This reaction was chosen because it is mechanistically well-understood and rates can be measured under kinetically limiting conditions and because it is catalyzed by FeN x centers . Additional discussion of transport limitations can be found in Section 4.2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, the HQ oxidation rate could reflect contributions from these other species, e.g., FeO x and γ-Fe aggregates, reflected by eq : where TOF i (s –1 ) and N i (mol g –1 ) reflect the turnover frequency and surface site density of any species i . In the limiting case where TOF FeNx is much larger than the TOF of any other species, the HQ oxidation rate can be used to calculate the FeN x site density on any Fe-N-C material according to eq : FeO x species , and Fe/Fe 3 C species show low ORR reactivity on their own, especially in acidic medium, and our prior study showed that the coexistence of aggregated Fe species with FeN x species on Fe-N-C catalysts leads to a lower HQ oxidation rate (per total Fe) than on Fe-N-C catalysts containing only FeN x species . These observations are consistent with the assumptions that led to eq .…”
Section: Resultsmentioning
confidence: 99%
“…18 Another work also demonstrated the solution-phase metalation of MVN4 sites in N-C support induced by zinc. 24 More recently, our group used Ni to introduce MVNx sites and synthesized Ni-MNx-C catalysts (M = Co 2+ , Fe 2+ , Fe 3+ ) for ORR via a solution-phase coordination approach, without any further heat-treatment. 25 It is not surprising to notice that these recent works using the solution-phase coordination methods mostly utilized sacrificial metal cations and target metal ions with the oxidation state of +2, including Zn 2+ , Mg 2+ , Ni 2+ , Fe 2+ , and Co 2+ , for their similarity in terms of favored coordination configuration with the Nx-sites.…”
Section: Introductionmentioning
confidence: 99%